P300 Modulation via Transcranial Alternating Current Stimulation in Adult Attention-Deficit/Hyperactivity Disorder: A Crossover Study - Kannen, Kyra; Aslan, Behrem; Boetzel, Cindy; Herrmann, Christoph S.; Lux, Silke; Rosen, Helena; Selaskowski, Benjamin; Wiebe, Annika; Philipsen, Alexandra; Braun, Niclas (Frontiers in Psychiatry, 2022)
Objective: A repeated finding regarding event-related potentials (ERP) is that patients with ADHD show a reduced P300 amplitude. This raises the question of whether the attention of ADHD patients can be increased by stabilizing the P300. Assuming that the P300 is generated by event-related oscilla-tions (ERO) in the low frequency range (0-8 Hz), one approach to increase the P300 could be to stimu-late the patient's P300 underlying ERO by means of transcranial alternative current stimulation (tACS). The aim of this replication study was to investigate this hypothesized mechanism of action in adult ADHD patients. Methods: Undergoing a crossover design, n = 20 adult ADHD patients (10 female) received an actual stimulation via tACS on one day and a sham stimulation on another day. Before and after each interven-tion, EEG characteristics (P300 amplitudes, low frequency power) and attention performances (d2 at-tention test, visual oddball task) were recorded. Results: Electrophysiological analyses revealed no evidence for a stronger P300 amplitude or low fre-quency power increase after actual stimulation compared to sham stimulation. Instead, a trend was found for a stronger N700 amplitude increase after actual stimulation than sham stimulation. Consistent with the P300 null results, none of the examined neuropsychological performance measures indicated a tACS-induced improvement in attentional ability. Conclusion: Contrary to a previous study using tACS to modulate the P300 in adult ADHD patients, the current study yields no evidence that tACS can increase the P300 amplitude in adult ADHD patients and that such P300 enhancement can directly improve neuropsychological parameters of attention.